A lightweight and low-cost electrode for lithium-ion batteries derived from paper towel supported MOF arrays. Issue 43 (27th April 2020) - Zhu, Longzhen; Yao, Zhifan; Liu, Tianqing; Xu, Chao; Cai, Daoping; Sa, Baisheng; Chen, Qidi; Zhan, Hongbing
Abstract : Cu-Doped Co/CoO/NC hybrid nanoplate arrays grown on a paper towel derived carbon paper substrate are synthesized and exhibit excellent performance as a low-cost and lightweight binder-free electrode for lithium-ion batteries. Abstract : Herein, Cu-doped Co-ZIF nanoplate arrays are uniformly grown on a commercial paper towel substrate first. After a subsequent annealing treatment, well-defined Cu-doped Co/CoO nanoparticles embedded in N-doped carbon hybrid nanoplate arrays supported on the carbon paper substrate (denoted as Cu-doped Co/CoO/NC NPAs@CP) are obtained, which exhibit excellent performance as a low-cost, lightweight and binder-free anode for lithium ion storage.